Study on the concentration of isooctane from oleic acid - Mohd Shahli, Mohd Sidek (2008)
The purpose of analyzing and determination of the concentration of biopetrol obtained from oleic acid is to determine the quantitative amount of biopetrol required in future. Biopetrol is the latest finding in research of renewable liquid fuel and regarding on research that has being done, biodiesel that produced from vegetable oils can reduce emission of pollutants. In this study, oleic acid will be used as the raw material and thermal cracking method is used. Simple distillation at various temperatures which is 98oC, 200oC, 280oC, 320oC and 360oC is used to crack the long oleic acid chain to form biopetrol. The heat required will cracks the sample’s molecular bonds randomly into small hydrocarbon radicals, followed by random isomerization of these radicals to form a mixture of new chains of alkanes with isooctane as the major component subjected. After cracking process, the sample is analyzed using Gas Chromatography method with comparison of the standard isooctane as reference. The results obtained from the analysis show that isooctane exists in the sample at retention time of 2.140 at average by comparing with standard isooctane calibration curve. The concentration of the Isooctane after cracking process is at various temperatures is in between 0.4 % to 3.4 %. This experiment is a success because the concentration of the desired component has being determined. increasing of time of heating will decrease the degree of deacetylation.